2022
DOI: 10.22421/1517-7130/es.2022v23.e836
|View full text |Cite
|
Sign up to set email alerts
|

Space-time clusters of severe acute respiratory syndrome and COVID-19 and hierarchical urban network in the state of Mato Grosso, Brazil, 2020-2021

Abstract: Objective: to analyze the space-time distribution of COVID-19 in the state of Mato Grosso, Brazil. Methods: Weekly case records of Severe Acute Respiratory Syndrome were obtained from the Ministry of Health’s Database related to this syndrome, including data from COVID-19. Temporal and spatiotemporal analysis using scanning statistics to identify clusters of severe acute respiratory syndrome cases were performed with the software SaTScan. Results: A total of 27,093 cases was observed, with an incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…A recent space-time analysis of cases of severe acute respiratory syndrome (SARS) and COVID-19 in 2020 and 2021 in Mato Grosso showed that the clusters were connected by the state's federal highways, urban connections, and hierarchical urban network 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent space-time analysis of cases of severe acute respiratory syndrome (SARS) and COVID-19 in 2020 and 2021 in Mato Grosso showed that the clusters were connected by the state's federal highways, urban connections, and hierarchical urban network 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The highway is the main marketing route for Mato Grosso, Brazil's leading grain-producing state 24 . It interconnects municipalities that are highly relevant in the urban hierarchy 23 ; many resulting from the intense migratory flow towards the agricultural frontier and the mining areas 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Recentemente, uma análise espaço-temporal dos casos de síndrome respiratória aguda grave (SRAG) e de COVID-19 nos anos de 2020 e 2021 em Mato Grosso revelou que os clusters são conectados por rodovias federais, conexões urbanas e pela rede urbana hierárquica do estado 23 .…”
Section: Indicadoresunclassified
“…A rodovia é a principal rota de escoamento de Mato Grosso, o maior produtor nacional de grãos 24 . Ela interliga municípios de grande relevância hierárquica urbana 23 ; muitos deles resultantes do intenso fluxo migratório rumo à fronteira agrícola e às áreas de garimpos 25 .…”
Section: Indicadoresunclassified